HIGH TEMPERATURE LOAD MEASUREMENT FOR NOZZLE COMPONENT OF A CERTAIN AERO-ENGINE - XU YanZhi; LEI XiaoBo; WEN Min; HU ChunXiao; ZHAO Bo (Jixie qiangdu)
T4 link is the critical load-bearing component for nozzle element of a certain engine. Whether the nozzle load meets the requirements or not at high temperature is the key factor in the structural integrity of the nozzle unit. It’s analyzed that strain response of the T4 link was resulted from mechanical load, thermal gradient and material parameter using the thermo-solid coupling method. The T4 link load at high temperature was measured with the high temperature strain gauge on bed test. The process for bonding and assembling the high temperature strain gauge was developed. the equation extension method of the load calibration was deduced, the measurement method containing load calibration, thermal correction, and date processing for the high temperature load were established. The aero-engine bed test shows that the variation tendency and value of the thermal-output strains vary much between T4 links. The maximum error for T4 link is 0.27 kN, the maximum measured tension is 62.1% of the designed load value, the maximum pressure is 58.46% of the designed load value, and the structural strength design of T4 link meets the operating requirements.